Synthesis and electrochemistry of pseudocapacitive multilayer fullerenes and MnO2 nanocomposites - Azhagan, Muniraj Vedi Kuyil; Vaishampayan, Mukta V.; Shelke, Manjusha V. (Journal of Materials Chemistry A, 2014)
Electrode materials with efficient capabilities for ionic and electronic transport are key to high performance supercapacitors. Here, we demonstrate a simple and comparatively low temperature synthesis of functionalized multilayer fullerenes so called carbon nano-onions (CNOs) as the electrode for high performance electrochemical supercapacitors. The exohedral type supercapacitor formed due to nonporous CNOs showed higher specific capacitance than conventional graphitic/mesoporous/activated carbons. Surface redox functionalities of these CNOs add up to significant pseudocapacitance. Further in situ incorporation of MnO2 nanoparticles to these CNOs increased the specific capacitance up to 1207 F g(-1), which is close to the theoretical value of pseudocapacitive MnO2.